2012
DOI: 10.1007/s00011-012-0512-0
|View full text |Cite
|
Sign up to set email alerts
|

The anti-inflammatory effects of platinum nanoparticles on the lipopolysaccharide-induced inflammatory response in RAW 264.7 macrophages

Abstract: These results suggest that the anti-inflammatory properties of nano-Pt may be attributed to their downregulation of the NFκB signaling pathway in macrophages, thus supporting the use of nano-Pt as an anti-inflammatory agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 67 publications
4
76
0
Order By: Relevance
“…The anti-oxidant properties of CeO 2 NPs thus depend on the nanocrystal diameter (Lee et al, 2013) and the ratio of surface Ce 3+ /Ce 4+ (Das et al, 2012). This interesting anti-oxidant property of some nanomaterials is intended to be used in nanomedical applications (Colon et al, 2010, Rehman et al, 2012). …”
Section: 2 Hierarchical Oxidative Stress Modelmentioning
confidence: 99%
“…The anti-oxidant properties of CeO 2 NPs thus depend on the nanocrystal diameter (Lee et al, 2013) and the ratio of surface Ce 3+ /Ce 4+ (Das et al, 2012). This interesting anti-oxidant property of some nanomaterials is intended to be used in nanomedical applications (Colon et al, 2010, Rehman et al, 2012). …”
Section: 2 Hierarchical Oxidative Stress Modelmentioning
confidence: 99%
“…In pathogenic conditions, abnormally activated macrophages produce excessive amounts of various proinflammatory mediators and cytokines that eventually aggravate inflammatory conditions. Lipopolysaccharides (LPSs), a component of the outer membrane of Gram-negative bacteria, are the most common cause of macrophage activation [2][3]. LPS-induced activation of macrophages causes a wide range of pro-inflammatory responses, such as production of pro-inflammatory mediators.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages play essential roles in the host defense against bacterial infection (Rehman et al , 2012). However, aberrant activation of macrophages plays detrimental roles in multiple inflammation-related disorders including sepsis by producing a wide range of pro-inflammatory mediators and cytokines (Rietschel and Brade, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Although macrophages play essential roles in the mobilization of the host defense against bacterial infection (Rehman et al , 2012), aberrant activation of macrophages has been also reported to play pathogenic roles in various inflammatory disorders including sepsis (Kim et al , 2012). In pathogenic conditions, abnormally activated macrophages produce excessive amount of a variety of pro-inflammatory mediators and cytokines that eventually aggravates the inflammatory conditions (Itharat and Hiransai, 2012).…”
Section: Introductionmentioning
confidence: 99%